STUDENTS’ AND ENGLISH TEACHERS’ PERSPECTIVE ON THE IMPLEMENTATION OF ENGLISH DAY (A Study of 12th Grade at MAWARIDUSSALAM ISLAMIC BOARDING SCHOOL) 2023-2024 - Br Ginting, Lady Prisma; Sihite, Meida Rabia; Lubis, Sofia Idawati (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
The objective of this research was to determine Students’ and English Teachers’ Perspective on the Implementation of English Day (A Study of 12th Grade at Mawaridussalam Islamic Boarding School). This research method is applied a qualitative research, data were collected from questionnaire, interviews. The sample of this research is the students of class 12th grade of Mawaridussalam. The writer uses questionnaire and interview guidelines. The results of this study indicated that the English day program can improve students' English skills. However, the implementation of English day at Mawaridussalam has not been carried out well because: some students still use Indonesian during English day, some students are not confident to speak English with friends around them, there is anxiety in the because they are afraid of making mistakes when speaking English, and sometimes they still make mistakes in writing or pronunciation. It is recommended that LIC (language improvement council and CLI (central language improvement) be more sensitive and strengthen the rules so that all students do not violate the rules and can overcome existing obstacles..